IMPLEMENTASI PENGELOLAAN KEUANGAN PUSKESMAS SETELAH BERSTATUS MENJADI BLUD (STUDI KASUS DI PUSKESMAS MAGELANG SELATAN) - Hernita Sulistyowati; Suci Nasehati Sunaningsih (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
Puskesmas as a Regional Public Service Agency, has the opportunity to improve services to the community by implementing the flexibility of BLUD financial management. The South Magelang Health Center is one of the main health centers in Magelang City, which has changed to become a BLUD since 2013. The purpose of this study was to assess and identify the obstacles faced in the implementation of the financial management of the South Magelang Health Center based on the flexibility of the BLUD. The method used is a qualitative descriptive approach that emphasizes case studies. Collecting data through in-depth interviews, documentation and observation. The results showed that the Puskemas had implemented 5 out of 10 BLUD flexibility, namely income flexibility, expenditure management, procurement of goods and services, cooperation, and SiLPA/deficit management. The Puskesmas also already has a financial management SOP to make financial management more organized. The obstacle that is still faced by the Puskemas is that there is no Magelang Mayor's Regulation that regulates some BLUD flexibility, so that the Puskemas are not been able to apply the flexibility optimally.